Legal Protection for Taxpayers in Income Tax Disputes in the Tax Court - Siti Aisyah; Halwa Nisa Ali Br. Tarigan; Halimatusadiah; Erna Wati; Dimas Nugroho (Jurnal Cendikia ISNU SU, 2024)
Tax disputes, particularly those related to Income Tax (PPh), are a frequent issue in the relationship between taxpayers and tax authorities in Indonesia. In many cases, taxpayers feel disadvantaged by tax authorities' decisions that do not reflect the actual situation, thus giving rise to the need for adequate legal protection, particularly in the Tax Court process. This study aims to analyze the forms of legal protection for taxpayers in PPh disputes and to identify obstacles and opportunities within the tax justice system. The research method used is normative juridical with a statutory approach and case studies, supplemented by an analysis of Tax Court decisions. The results indicate that legal protection for taxpayers is normatively available through objection, appeal, and lawsuit mechanisms. However, in practice, various obstacles remain, such as limited access to legal aid, the tax authority's dominance in the burden of evidence, and the unequal position between taxpayers and tax authorities. In addition, some court decisions still do not fully reflect substantive justice for taxpayers. Therefore, a reform of the tax dispute system is needed to be more inclusive, transparent, and ensure equality between the parties. This research is expected to contribute to the development of a fair tax legal protection system in Indonesia.